If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = 3x + 75 Reorder the terms: 12 + 6x = 3x + 75 Reorder the terms: 12 + 6x = 75 + 3x Solving 12 + 6x = 75 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 6x + -3x = 75 + 3x + -3x Combine like terms: 6x + -3x = 3x 12 + 3x = 75 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 3x = 75 + 0 12 + 3x = 75 Add '-12' to each side of the equation. 12 + -12 + 3x = 75 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 75 + -12 3x = 75 + -12 Combine like terms: 75 + -12 = 63 3x = 63 Divide each side by '3'. x = 21 Simplifying x = 21
| 2(4x+2)=5x-32 | | 5p^2=60+20p | | 8p-15=4p-3 | | 2w+5=15-3w | | 3m-8m-6=64 | | 3/4x-3/8=1/2y | | 2p=14-5p | | 2x+4=106 | | 10(.30)=x(.5) | | x-12+6=2 | | -53-10x=101-45x | | 8x-15y=3 | | 10(.25)=x(.5) | | g(x)=2x^2-11X+15 | | 5v-15=80 | | 10a+47=239 | | 7x-22=360 | | 13m+6n-5m+11n= | | (4x+8)(5x-20)=0 | | 12x-15=3x+107 | | (2x-y)(3x-2y)= | | [3n-2]+9=8 | | 5x-21=x+19 | | 12x+y=19 | | .003x^2-.04x+.12=0 | | 4/3x-1=47 | | y-7=5x-35 | | 36x^2-35x-1=0 | | 6y+7o-8y+9o= | | 4x+4x=5.5 | | 4(4w+9)= | | y-2=5x-10 |